The effects of dietary supplementation with red grape pomace treated with ozone gas on ruminal fermentation activities, nutrient digestibility, lactational performance, and blood metabolites in dairy ewes - Behzad Asadnezhad; Rasoul Pirmohammadi; Yonesali Alijoo; Hamed Khalilvandi-Behroozyar; Hossein Abdi-Benmar; Deli Nazmín Tirado-González; Pedro Enrique Hernández Ruiz; Valente Velazquez Ordoñez; Maximilian Lackner; Abdelfattah Z.M. Salem (Journal of Agriculture and Food Research)
This study aimed to investigate the effect of red grape pomace (RGP) treated with ozone (O3) gas as a substitute of low-quality alfalfa hay on the ruminal fermentation, nutrient digestibility, and milk production performance of fat-tailed, fed RGP substituted high fibrous alfalfa hay. Present study was performed in two experimental phases: 1) In situ and in vitro phase: Four Ghezel ewes in their third gestation (30 months old; weighing 51 ± 2 kg) with surgically implanted cannulas in their rumen were used to assess the in situ degradability and to obtain ruminal fluid to assay the in vitro gas production; the treatments were RGP not-processed (control; T0), and RGP processed with O3 for 6 (T1), 12 h (T2), and 24 h (T3). Processing RGP with O3 gas reduced (P < 0.05) neutral detergent fiber (NDF) and acid detergent fiber (ADF), although the processing time did not show differences. Ozone-treated RGP caused a reduction (P < 0.02) in total phenolics, total tannins, condensed tannins, protein-bound tannins, and fiber-bound tannins, compared to the control. Processing RGP with O3 for 12 h improved the nutritional value of RGP because of the reduction of the concentration of phenolic compounds, the increase of the in vitro gas production and the dry matter (DM) degradability, and improved fermentation parameters and it was chosen for the second phase of the experiment. 2) In vivo phase: Forty-eight healthy multiparous fat-tailed Ghezel ewes received the control diet (0 % RGP), or diets that substituted 20, 40, and 60 % of the dietary alfalfa hay with RGP processed with O3 for 12 h. Incremental dietary replacement of RGP with alfalfa hay did not influence the ruminal total volatile fatty acids but increased (P < 0.03) propionate. The digestibility coefficients of the DM and the NDF increased (P < 0.001) in diets containing RGP versus the control, but not for the crude protein and ether extract. The ruminal protozoa population exhibited a linear increase with the addition of O3-treated RGP (P < 0.001). Plasma glucose and albumin concentration increased (P < 0.04), and milk production and milk fat, protein, and lactose contents also increased (P < 0.05) with the alfalfa substitution with O3-processed RGP. In conclusion, replacing high-fibrous alfalfa hay with RGP treated with O3 for 12 h improved the apparent digestibility of DM and NDF and maintained the performance of the ewes.